2020
DOI: 10.2196/21108
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Telepsychiatry: Development of Evidence-Based Guidance for Clinicians

Abstract: Background The coronavirus disease (COVID-19) presents unique challenges in health care, including mental health care provision. Telepsychiatry can provide an alternative to face-to-face assessment and can also be used creatively with other technologies to enhance care, but clinicians and patients may feel underconfident about embracing this new way of working. Objective The aim of this paper is to produce an open-access, easy-to-consult, and reliable s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 21 publications
5
131
1
2
Order By: Relevance
“…An added value of digital mental health is that it may be designed for automated thematic and metadata review, traceability for quality assurance, and assignment of responsibility for identified cases of mental ill health. Existing telepsychiatry guidelines (including other relevant digital technologies) should be considered [ 23 ] for a consistent and consolidated knowledge management strategy for integrated services. Consensus, expert, and position statements are required from psychiatrists, psychologists, and academic researchers on the individual, cultural, and environmental factors that affect the well-being of the patient with suggestions for brief, valid and reliable screening and tracking surveys for the prevention and treatment of mental health symptoms and disorders.…”
Section: Resultsmentioning
confidence: 99%
“…An added value of digital mental health is that it may be designed for automated thematic and metadata review, traceability for quality assurance, and assignment of responsibility for identified cases of mental ill health. Existing telepsychiatry guidelines (including other relevant digital technologies) should be considered [ 23 ] for a consistent and consolidated knowledge management strategy for integrated services. Consensus, expert, and position statements are required from psychiatrists, psychologists, and academic researchers on the individual, cultural, and environmental factors that affect the well-being of the patient with suggestions for brief, valid and reliable screening and tracking surveys for the prevention and treatment of mental health symptoms and disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 illness and governments’ attempts to manage its spread bring a range of new social, physical and psychological risks for clinicians to consider (see https://oxfordhealthbrc.nihr.ac.uk/our-work/oxppl/covid-19-and-mental-health-guidance). Acceptance and uptake of telepsychiatry has accelerated during the pandemic, with consequences for all aspects of professional practice (Smith et al, 2020). As we note below, a key challenge for clinicians is keeping abreast of technological developments, which emerge not through traditional scientific processes (across time frames of years), but through the marketplace (across time frames of months).…”
Section: Introductionmentioning
confidence: 99%
“…However, the forced adoption of and mass transition to telehealth during the COVID-19 pandemic has resulted in significant challenges for the implementation of telehealth for psychiatric services [ 9 , 10 ]. While guidelines exist for postpandemic telepsychiatry [ 11 , 12 ], given the unique characteristics of this COVID-19 pandemic, lessons learned from these transitions as well as implementation-specific guidelines would be highly applicable to other practices. To date, clinical implementations and lessons learned (and with largely positive results) have been reported largely from settings outside the United States, such as China [ 13 , 14 ], Europe [ 15 - 23 ], Turkey [ 24 ], and Australia [ 10 , 25 - 28 ], with only some US coverage (notably [ 9 ], [ 29 ], and [ 30 ]).…”
Section: Introductionmentioning
confidence: 99%